Synthesis, Optical Properties, and Sensing Applications of LaF3:Yb3+/Er3+/Ho3+/Tm3+ Upconversion Nanoparticles - Hsiu-Wen Chien; Chien-Hao Huang; Chien-Hsin Yang; Tzong-Liu Wang (Nanomaterials, 2020)
Herein, we successfully synthesized a series of LaF3:Yb3+/Er3+/Ho3+/Tm3+ upconversion nanoparticles (UCNPs) and LaF3:Yb3+0.20, Er3+0.02@LaF3:Yb3+0.20 core/shell UCNPs by modifying the amount of NaOH and the reaction time. Hexagonal LaF3 nanocrystals with uniform particle sizes and bright UC emissions were obtained. The crystal structures of the lanthanide-doped LaF3 UCNPs were investigated using wide-angle X-ray diffraction. The morphologies and particle sizes of the nanocrystals were determined using transmission electron microscopy. The photoluminescence (PL) spectra of the LaF3 nanocrystals could be tuned by altering the doping ratio of Er3+, Ho3+, and Tm3+. In addition, the PL intensities increased after coating the UCNP cores with an active shell. The fluorescence intensities of the UCNPs synthesized via a one-hour reaction with the addition of 2.5 or 5 mmol NaOH increased by up to 17 times compared with the sample prepared without the addition of NaOH. By modifying the doping ratio of Yb/Tm, UV-emissive LaF3 nanocrystals were obtained. After surface modification by ligand exchange, the hydrophobic LaF3:Yb3+0.20, Er3+0.02@LaF3:Yb3+0.20 core/shell UCNPs became water-dispersible. These colloid UCNPs could be utilized as a fluorescent probe for the detection of Hg2+ ions under 980 nm near-infrared irradiation.